An experimental approach for shear strengthening of RC beams using a proposed technique by embedded through-section FRP sheets. (15th April 2020) - Moradi, E.; Naderpour, H.; Kheyroddin, A.
Abstract: This article presents a new technique for enhancing the shear capacity of RC beams with FRP materials, which instead of bonding of FRP strips on the external face of element, involves perforating holes along the beam web, inserting FRP reinforcement inside these holes, and filling the holes with grout. Although according to technical literature, externally bonded and near-surface mounted FRP reinforcements are well known as effective solutions for increasing the shear capacity of RC elements, they are ill-suited for the cases where the concrete cover lacks sufficient bonding strength, and a debonding may allow the beam to fail before maximum capacity utilization. Furthermore, in the structures where the beam is connected to a floor, the FRP wrapping involves drilling holes in the floor to install the reinforcement, which creates shear vulnerability around the floor-beam contact area. Experimental results show that the beams reinforced with the proposed technique perform similar to or better than those with externally bonded FRP reinforcements. Also, the comparisons of the Applied Strengthening Material Index (ASMI) for specimens shows that the ratio of FRP shear contribution to the amount of FRP consumed is greater in the proposed technique than in the external bonding methods.